The rehabilitation of physical function after severely disabling stroke: a survey of UK therapist practice. (2nd July 2021) - McGlinchey, Mark P; McKevitt, Christopher; Faulkner-Gurstein, Rachel; Sackley, Catherine M
Abstract : Background/aims: Individuals who are severely disabled from stroke (survivors of severely disabling stroke) experience poorer outcomes compared to those who are less disabled from stroke. However, there is a paucity of evidence describing current therapy practice in the management of severely disabling stroke. The aim of the study was to describe intervention and outcome measure use by physiotherapists and occupational therapists in the rehabilitation of physical function of survivors of severely disabling stroke. Methods: A mixed-methods survey was conducted, involving an online questionnaire and follow-up interviews. Survey participants were UK-based physiotherapists and occupational therapists with experience treating stroke. Questionnaire data were analysed with descriptive and inferential statistics. Interview data were analysed using content analysis. Results: A total of 452 therapists (59% physiotherapists) responded to the questionnaire. Out of the respondents, 18 self-selected therapists participated in follow-up interviews to explain questionnaire data. Whole body positioning, training of upper limb handling and positioning, and sitting balance practice were the most frequently used interventions. Inpatient-based therapists performed more active rehabilitation interventions, whereas community-based therapists performed more training and education. The Barthel Index, Modified Rankin Scale and National Institutes for Health Stroke Scale were the most frequently used outcome measures. Outcome measure use was generally low and was more likely to be completed when it was part of a national audit. Reasons for low outcome measure use were perceived lack of time and insensitivity to detect clinical change. Conclusions: A variety of interventions and outcome measures are used in the rehabilitation of survivors of severely disabling stroke. There is a need to evaluate the effectiveness of frequently used interventions and identify outcome measures that are sensitive to the needs of survivors of severely disabling stroke.